Kangaroo mother care - a simple measure to save the low birth weight babies - Parveen Mittal ,; Navneet Kaur, (GMC Patiala Journal of Research and Medical Education, 2019)
Kangaroo Mother Care-skin to skin contact between the mother and her newborn is the most feasible, low cost and preferred intervention for decreasing morbidity and mortality among low birth weight babies. It has significant role in thermal regulation, preventing hypothermia, sepsis and regulation of vital physiological parameters. It helps in initiation of breastfeeding in newborns. It is an easy and effective method to promote health and well being of Low birth weight babies.